Employment performance in the member states : employment rates report 1998 - European Commission. Directorate-General V Employment, Industrial Relations and Social Affairs (Employment & social affairs, Employment & European Social Fund, 1999)
Summary (s. 7).
Keywords: työllisyys : EU-maat; työllisyys : naiset : EU-maat; työllisyys : nuoret : EU-maat; työllisyys : sukupuoli : EU-maat; työllisyys : tilastot : EU-maat